FLUCTUATIONS OF SEA ICE EXTENT IN THE ANTARCTIC - エノモト, ヒロユキ; オオムラ, アツム; ENOMOTO, Hiroyuki; OHMURA, Atsumu (National Institute of Polar Research, 1991)
P(論文) The sea ice area in the Antarctic is large in winter, while most of the sea ice melts in summer. This seasonal difference in coverage is very large, approximately the area of the Antarctic continent. In this study, characteristics of the normal seasonal change of sea ice area, such as seasonal asymmetric behavior of ice extent and change of sea ice concentration are investigated using a 12 yearlong weekly sea ice data set for the Antarctic. The week to week fluctuations of the open water area in the sea ice area are observed to be large in spring. The open water area in the sea ice area plays an important role in the movement of sea ice. Drastic change of the open water area is observed at the beginning and end of the freezing period. The characteristic scales in time and space for sea ice movements are obtained from spectral analyses. Some conditions of synoptic scale could be important for the movement of sea ice. departmental bulletin paper